The cytotoxic effects of MgO nanoparticles on human blood mononuclear cells - A Barkhordari; S Barzegar; H Hekmati Moghaddam; A Jebali; H Fallahzadeh (طب کار)
Introduction: The extended use of nanoparticles has increased and public concern about possible adverse health effects of exposure to this substance is growing. This study was conducted to assess the cytotoxic effects of different concentrations of MgO nanoparticles on human blood mononuclear cells. Methods: In this laboratory trial study, suspensions of blood mononuclear cells were prepared from 10 young healthy men and then were incubated with different concentrations of the nanoparticles (1, 10, 100, 500, 1000 and 1500 µg/ml) at 37 °c, and finally the percent of dead cells were measured by MTT assay after 6 and 24 hours of incubation. Positive and negative controls were also applied. Results: According to the results, the minimum and maximum death rate for 1 and 1500 µg/ml after 6 hours exposure was 30.9% and 44.7%, whereas for 24 hrs. Incubation was 26.5% and 64.4%, respectively. A significant difference was found in percent of dead cells in 1000 µg/ml. The highest toxicity of nanoparticles was found after 24 hrs. from 500 µg/ml and afterward. Significant difference was also found between the exposed cells and control group (p<0.05). Conclusion: This study showed that the toxicity of human blood mononuclear cells are dependent on both concentration and incubation time. In addition, LC50 was determined for 600 µg/ml just for 24 hours exposure.